ANALISIS PELAYANAN MUTU TOTAL DAN PENGARUHNYA TERHADAP KINERJA USAHA PERBANKAN DI INDONESIA - Tatik Suryani; Sri Lestari Kurniawati; Wiwik Lestari (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
This research explains the implementation of total quality service (TQS) in the banking industry in Indonesia and examines the differences of the implementation between government banks and private banks and also the influence of TQS variables on business performance. By using 32 samples, the result of regression analysis shows that TQS implementation variables significantly influence all banking performance variables, ie. human resources performance, customer satisfaction, service quality and cost performance except in financial performance variable at 5% level of significance. Further, there is significant difference between government banks and private banks in giving responses to their customers. Private banks give better response compared with those of government banks